Understanding How Older Adults with Communication Difficulties Access Health Services: What We Can Learn from the National Health and Aging Trends Study (NHATS) - Baylor, Carolyn; Brown, Cait; Mroz, Tracy M.; Burns, Michael (Seminars in Speech and Language, 2022)
People with communication disorders face barriers to accessing safe and respectful healthcare. These barriers result in increased healthcare complications and inefficiencies, both of which contribute to increased healthcare costs. One obstacle to advocating for accommodations that could improve healthcare for this population is the absence of cost effectiveness studies of such accommodations specifically, as well as a paucity of data defining the needs of this population in general. The purpose of this study was to explore how people with communication and swallowing difficulties are characterized in the National Health and Aging Trends Study (NHATS), a nationally representative survey of Medicare beneficiaries aged 65 and older, and how they manage their healthcare. Cross-sectional data from the NHATS rounds 5 to 9 (2015–2019) resulted in 8,038 unique respondents, 3,243 of who reported speech, memory, hearing, and/or swallowing difficulties. More than 90% of respondents with communication difficulties reported having a regular doctor. Less than 60% of respondents with communication difficulties had a family member or caregiver go to medical appointments with them, and around 70% of that subset of participants received help from that caregiver with communication during appointments. Fewer than 15% of respondents with communication difficulties used the internet for healthcare communication or information. Less than 5% of respondents across all communication difficulty categories had received rehabilitation services for communication in the year prior to their survey responses. While the information gleaned from NHATS points to likely gaps between the needs people with communication disorders may have for safe and accessible healthcare, and the support available, future research is needed to improve and clarify how communication disorders are defined and characterized in large-scale surveys to generate more interpretable data. These stronger empirical foundations are needed to support cost-effectiveness analyses to advocate for better communication accessibility of healthcare settings.
Keywords: communication disorders; healthcare accessibility; healthcare costs